(3TQM GdbhGYOs - (3GdeXaQ, eMeO MSf Hf eMeO, J (B1375 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeGFg (B...(3hajg CHhGH GdChd aj RcGI GdeGd hajg ebGUO GdChd aj TQGFW GdhLhH GdYGeI dLejY CehGd GdRchjI hgj hgj CQHYI GdChd GdHdhZ (B...s
(3BNQgG (B:s
.. (3hcd ef jbhdg ddJNjQ TQYG Hjf GdCfhGY GdOGdI Ydi GdeSGhGI HjfgeG cdG hCHYGVG hdjS PcQ GdUGY ef fhY hGMO aj GdCNHGQ XGgQG aj GdTQWjI hGdCUd YOegG (B..(3Je bSe GdRcGIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B9\219s
(3eYLe GdeDdajf (B9\219s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis